Vibrodinamic monitoring of pile foundation engineering on landslide hazardous site in dense urban development conditions - Kaliukh, Iurii I.; Lebid, Oleksij G.; Dunin, Volodimyr A.; Margvelashvili, Nugzar; Berchun, Yaroslav O.; Samoilenko, Sergiy M. (ІТГІП, 2018)
An example of the application of modern regulatory requirements for the scientific and technical support of construction and monitoring of building structures for the safe arrangement of the pile foundation on a landslide hazardous building site in conditions of dense urban development in Kyiv during the installation of a Ø820 mm bored pile according to the plan of the pile field has been considered. Experimentally registered levels of vibration acceleration on the foundation wall of the building in the vertical and horizontal directions do not exceed 0.015 m/s², which is significantly lower than the minimum permissible values of vibration acceleration for the foundations of buildings with brick bearing walls 0,15 m/s². The research also evaluated the presence of visible damage to the building in the available places and their possible development before and after piles placement. The condition of the plaster screed on a vertical crack in the wall of the house on the 8th floor, which was installed before the start of construction work, after pile foundation installation has not changed – it remained undamaged.
Keywords: safety; monitoring; pile; technical condition; sensor; vibroacceleration; 624.155:624.131.31]:519.7